Role of Prosopis cineraria against N-nitrosodiethylamine-induced liver tumor in rats with reference to marker enzymes and nucleic acid contents (Bangladesh Journal of Pharmacology, 2012)
The effect of methanol extract of Prosopis cineraria against experimental liver tumor in rats was studied. Liver tumor was induced by the administration of N-nitrosodiethylamine (200 mg/kg) and it was promoted by phenobarbital administration. Methanol extract (200 and 400 mg/kg) was administered to determine the protective activity. Administration of methanol extract suppressed the liver tumor effectively as revealed by  the decrease in elevated levels of aryl hydrocarbon hydroxylase, lactate dehydrogenase, g-glutamyl transpeptidase (g-GTP), 5nucleotidase, deoxyribonucleic acid (DNA) and ribonucleic acid (RNA). We found that methanol extract may extend its protective role by modifying the levels of  marker enzymes and nucleic acid contents.